Inferring episodic atmospheric iron fluxes in the Western South Atlantic - Evangelista, Heitor; Maldonado, Juan; dos Santos, Elaine A.; Godoi, Ricardo H. M.; Garcia, Carlos A. E.; Garcia, Virginia M. T.; Jonhson, Erling; Dias da Cunha, Kenya; Leite, Carlos Barros; Van Grieken, René; Van Meel, Katleen; Makarovska, Yaroslava; et al. (Atmospheric Environment)
Iron (Fe) and other trace elements such as Zn, Mn, Ni and Cu are known as key-factors in marine biogeochemical cycles. It is believed that ocean primary productivity blooms in iron deficient regions can be triggered by iron in aeolian dust. Up to now, scarce aerosol elemental composition, based on measurements over sea at the Western South Atlantic (WSA), exist. An association between the Patagonian semi-desert dust/Fe and chlorophyll-a variability at the Argentinean continental shelf is essentially inferred from models. We present here experimental data of Fe enriched aerosols over the WSA between latitudes 22°S–62°S, during 4 oceanographic campaigns between 2002 and 2005. These data allowed inferring the atmospheric Fe flux onto different latitudinal bands which varied from 30.4 to 1688 nmolFe m−2 day−1 (October 29th–November 15th, 2003); 5.83–1586 nmolFe m−2 day−1 (February 15th–March 6th, 2004) and 4.73–586 nmolFe m−2 day−1(October 21st–November 5th, 2005). Fil: Evangelista, Heitor. Universidade Federal do Rio de Janeiro; Brasil Fil: Maldonado, Juan. Universidade Federal do Rio de Janeiro; Brasil. Universidade Federal Fluminense; Brasil Fil: dos Santos, Elaine A. Universidade Federal do Rio de Janeiro; Brasil Fil: Godoi, Ricardo H. M. Universidade Federal do Paraná; Brasil Fil: Garcia, Carlos A. E. Universidade Federal do Rio Grande do Norte; Brasil Fil: Garcia, Virginia M. T. Universidade Federal do Rio Grande do Norte; Brasil Fil: Jonhson, Erling. Universidad de Magallanes; Chile Fil: Dias da Cunha, Kenya. Pontifícia Universidade Católica do Rio de Janeiro; Brasil Fil: Leite, Carlos Barros. Pontifícia Universidade Católica do Rio de Janeiro; Brasil Fil: Van Grieken, René. Universiteit Antwerp; Bélgica Fil: Van Meel, Katleen. Universiteit Antwerp; Bélgica Fil: Makarovska, Yaroslava. Universiteit Antwerp; Bélgica Fil: Gaiero, Diego Marcelo. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Córdoba. Centro de Investigaciones en ...